1996
DOI: 10.3109/10428199609045722
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Bcl-2 with P-Glycoprotein Expression in Chronic Lymphocytic Leukaemia and Other Haematological Neoplasms but of Neither Marker withEx VivoChemosensitivity or Patient Survival

Abstract: We compared bcl-2 with P-glycoprotein expression (C494 and JSB1), and both with ex vivo chemosensitivity by Differential Staining Cytotoxicity (DiSC) assay (25 cytotoxic drugs), in 76 fresh haematological specimens, including 51 chronic lymphocytic leukaemias (CLL). Strong correlations were seen between bcl-2 and Pgp expression in both CLL (r = 0.5; p < 0.001) and AML (r = 0.9; p < 0.001) although bcl-2 expression was only raised in Pgp positive cells. However, there was no correlation between high or low mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…[48][49][50] The role of the Bcl-2 family of proteins in chemoresponse has been evaluated extensively using in vitro models and it is still a matter of dispute whether individual members of the Bcl-2 family influence drug sensitivity of B-CLL cells in vitro. 3,25 Previous studies support our finding that Bcl-2 is not an important determinant of response to purine nucleoside analogs in B-CLL 51,52 perhaps because cladribine and fludarabine may directly activate the downstream apoptosis cascade, 34,35 ie the caspases 37,53 or other proteases 54,55 which are related to apoptotic and other modes of cell death. 56 That fludarabine and cladribine do not make use of the Bcl-2/Bax pathway is consistent with their efficacy in patients resistant to the traditional therapies.…”
Section: Leukemiasupporting
confidence: 77%
“…[48][49][50] The role of the Bcl-2 family of proteins in chemoresponse has been evaluated extensively using in vitro models and it is still a matter of dispute whether individual members of the Bcl-2 family influence drug sensitivity of B-CLL cells in vitro. 3,25 Previous studies support our finding that Bcl-2 is not an important determinant of response to purine nucleoside analogs in B-CLL 51,52 perhaps because cladribine and fludarabine may directly activate the downstream apoptosis cascade, 34,35 ie the caspases 37,53 or other proteases 54,55 which are related to apoptotic and other modes of cell death. 56 That fludarabine and cladribine do not make use of the Bcl-2/Bax pathway is consistent with their efficacy in patients resistant to the traditional therapies.…”
Section: Leukemiasupporting
confidence: 77%
“…This may be in some small part due to the use of¯udarabine in other chemotherapy later on and in part due to drug cross-resistance attributable to pleiotropic drug sensitivity in some untreated patients and pleiotropic drug resistance (but not multidrug resistance, MDR (Bosanquet et al, 1996)) in patients with advanced CLL. (Thus, patients test-resistant tō udarabine are more likely to be test-resistant to other CLL therapies.)…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of MDR + phenotype seems to be more frequent in males than in females with CLL (66) and this may link with the proposed better survival likelihood in women. However, an MDR + phenotype in CLL does not appear to correlate with either staging and clinical parameters (66,72), and/or in vivo or in vitro sensitivity to drugs (73). Expression of p-glycoproteins has been documented in CD19 + CD5 + B cells from tonsils and blood in normal individuals (71,74), and it has been suggested that p-glycoprotein expression may be an inherent characteristic of CLL cells.…”
Section: Multidrug Resistance Phenotypementioning
confidence: 99%